A Model for Responsible Governance of human-centric AI in the Public Sector - Niglia, Francesco (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Responsible AI Governance in the Public Sector is no longer an option due to the numerous ethical issues that have emerged in recent years with the adoption of AI-based services in the Public Sector. Given the numerous challenges AI poses, it is essential to incorporate human- centric and social perspectives. This study discusses a framework model for defining the roles, responsibilities, and skills of all the stakeholders involved in the processes of AI development, deployment, and assessment.